(untitled) (EU and comparative law issues and challenges series (ECLIC), 2024)
The social housing policies in many European Union (EU) member and candidate countries, coupled with challenges in the private property market, have resulted in an inability to adequately address the housing needs of low and middle-income households. Approximately one-third of the EU population resides in privately rented housing, prompting several member and candidate countries to implement rent controls due to a significant surge in rents within the private housing sector. These controls may involve setting rent ceilings, limiting the annual increase in rental rates, and other similar interventions. For instance, in Turkey, the legislature has imposed a 25% limit on the increase of rental prices in existing contracts over the past two years. It is noteworthy, however, that the official inflation rates declared by the government in 2022 and 2023 were almost three times higher than the rental increase limit imposed by the legislature. The implementation of such interventions has sparked debates on the compatibility of such rent controls with the constitutions of the relevant countries and the European Convention on Human Rights (ECHR). Various cases, including James and Others v the United Kingdom, Aquilina v Malta, and Urbárska Obec Trenčianske Biskupice v Slovakia, illustrate instances where the European Court of Human Rights (ECtHR) has addressed restrictions on landlords’ rights. According to the court, countries have a margin of appreciation in implementing such restrictions, but they must ensure that the limitations imposed are proportionate and guarantee fair and adequate rent. Several constitutional courts, including the Turkish Constitutional Court, have also examined the constitutionality of rent controls. The objective of this paper is to establish criteria for acceptable rent controls based on the decisions of the ECtHR and the constitutional courts of EU member and candidate countries. These criteria aim to guide policymakers in striking a balance between addressing housing challenges and respecting property rights and freedom of contract for landlords.